Identification Of Problems And Models Of Coastal Area Management Labuhan Village Sumbawa, District Labuhan Badas, Sumbawa - Ieke Wulan Ayu; Usman Usman; Edrial Edrial; Soemarno Soemarno (Journal of Aquaculture Science, 2021)
The coastal area of Labuhan Sumbawa Village has strategic value for economic development and improving people's welfare, but is very vulnerable to damage due to the use of multifunctional space, so that coastal management is urgently needed that focuses on regional characteristics, by placing three pillars of sustainable development, namely ecology, economy, and social. This study aims to identify problems and models of coastal area management in Labuhan Sumbawa Village, Labuhan Badas District, Sumbawa. The research method used is descriptive research method. Data was collected by means of observation and semi-structured interviews. Accidental sampling technique and qualitative data analysis. The results showed that in the coastal area of the research location, identified: (1) Physical damage to the environment, including: a) Damage to ecosystems (ecosystems, coral reefs, seagrass beds, and beaches); b) Damage to fish resources; c) Pollution; d) Abrasion, sedimentation, and siltation; and d) Natural disasters (floods); (2) Socio-economic problems, including: a) The problem of poverty and the low level of education of the population; b) Limited funds in development; and c) Lack of understanding of the value of coastal area resources; (3) Institutional problems, including: a) The problem of conflict of authority, which can occur due to sectoral development; b) The problem of legal uncertainty. The coastal area management models that can be applied are: (1) traditional management; (2) community-based coastal area resource management; (3) Co-management, and; (4) Ecosystem Based Fisheries Management (EBFM). The conclusion of the study is that damage to coastal areas will have an impact on ecological, economic, and social conditions so that multi-stakeholder involvement is very important in sustainable coastal area management. Keywords: Ecology, economy, social, coastal, model